Results of Gamma Knife Radiosurgery in Acromegaly - Franzin, Alberto (Hindawi Publishing Corporation, 2012)
Objective. Single-session radiosurgery with Gamma Knife (GK) may be a potential adjuvant treatment in acromegaly. We analyzed the safety and efficacy of GK in patients who had previously received maximal surgical debulking at our hospital. Methods. The study was a retrospective analysis of hormonal, radiological, and ophthalmologic data collected in a predefined protocol from 1994 to 2009. The mean age at treatment was 42.3 years (range 22–67 yy). 103 acromegalic patients participated in the study. The median follow-up was 71 months (IQ range 43–107). All patients were treated with GK for residual or recurrent GH-secreting adenoma. Results. Sixty-three patients (61.2%) reached the main outcome of the study. The rate of remission was 58.3% at 5 years (95% CI 47.6–69.0%). Other 15 patients (14.6%) were in remission after GK while on treatment with somatostatin analogues. No serious side effects occurred after GK. Eight patients (7.8%) experienced a new deficit of pituitary function. New cases of hypogonadism, hypothyroidism, and hypoadrenalism occurred in 4 of 77 patients (5.2%), 3 of 95 patients (3.2%), and 6 of 100 patients at risk (6.0%), respectively. Conclusion. In a highly selected group of acromegalic patients, GK treatment had good efficacy and safety.